Macroseismic Analysis of the 2023 Earthquakes in Jayapura - Bakhtiar, Takhul; Ahsan, Muh Nahdhi; Syawal, Muhammad; Pamuji, Danang (MO.RI Publishing, 2024)
On January 2 and February 9, 2023, two significant earthquakes struck Jayapura City, leading to widespread panic, severe damage to buildings and public infrastructure, and multiple casualties. In response, the BBMKG V Earthquake Survey Team conducted a macroseismic study to evaluate the geological impacts, assess community responses, and document the overall effects of the earthquakes. The methodology employed included structured interviews and questionnaires administered to affected residents. The study revealed that soft rock conditions in the area contributed to an MMI scale VI impact, which resulted in extensive damage to public facilities and residential buildings. The insights gained from this study offer valuable information for improving future earthquake mitigation strategies and enhancing preparedness in seismically vulnerable regions.